Aspects of the resilience and settlement of refugee youth: a narrative study using body maps/Aspectos da resiliência e da integração social de jovens refugiados: um estudo narrativo usando mapas corporais - Davy, Charity; Magalhães, Lilian Vieira; Mandich, Angela; Galheigo, Sandra Maria (Cadernos Brasileiros de Terapia Ocupacional, 2014)
Introduction: The primary concern of this study is to assist refugee youths in telling their transition story through art in order to understand facilitators and barriers to successful settlement in Ontario, Canada. Methods: This article briefly explains a new approach to visual methodologies, body mapping. Body maps are life-size human body images created through rawing, painting or other art-based techniques and can be developed with different purposes. In this project, these artifacts were used to elicit refugee youths’ life stories in a more neutral and meaningful way than standard interviews. Results: The participants’ migration journey is described in three phases: (1) pre-arrival; (2) arrival; and (3) settlement. Each participant is presented in a brief narrative story. The main themes presented in the data are discussed, namely faith, family, education, and future. Finally, the body maps and their application in health research addressing sites of (a) production, (b) image, and (c) audience are examined.